2016
DOI: 10.1186/s12916-016-0739-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of computer-based computer tomography stratification against outcome models in connective tissue disease-related interstitial lung disease: a patient outcome study

Abstract: BackgroundTo evaluate computer-based computer tomography (CT) analysis (CALIPER) against visual CT scoring and pulmonary function tests (PFTs) when predicting mortality in patients with connective tissue disease-related interstitial lung disease (CTD-ILD). To identify outcome differences between distinct CTD-ILD groups derived following automated stratification of CALIPER variables.MethodsA total of 203 consecutive patients with assorted CTD-ILDs had CT parenchymal patterns evaluated by CALIPER and visual CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
7
55
0
1
Order By: Relevance
“…In the current study, PVV and ILD extent, scored visually and with CALIPER, were independently predictive of FVC, DL CO and CPI, replicating findings in IPF . Whilst the pathophysiological basis of the CALIPER PVV signal is unclear, the results of the current study support previous findings in IPF and connective tissue disease‐related ILD, which suggested that the PVV signal may reflect a combination of both interstitial extent and vascular damage. As previously stated, whilst the majority of the PVV signal arises from the vasculature, in cases with more extensive fibrosis, the PVV measure may capture some perivascular fibrosis or peripheral reticulation, which may be reduced with refinement of the tool.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, PVV and ILD extent, scored visually and with CALIPER, were independently predictive of FVC, DL CO and CPI, replicating findings in IPF . Whilst the pathophysiological basis of the CALIPER PVV signal is unclear, the results of the current study support previous findings in IPF and connective tissue disease‐related ILD, which suggested that the PVV signal may reflect a combination of both interstitial extent and vascular damage. As previously stated, whilst the majority of the PVV signal arises from the vasculature, in cases with more extensive fibrosis, the PVV measure may capture some perivascular fibrosis or peripheral reticulation, which may be reduced with refinement of the tool.…”
Section: Discussionsupporting
confidence: 89%
“…with 5 and 7 years of thoracic imaging experience, respectively, blinded to all clinical information. Visual CT scoring and consensus derivation have been previously described . CT patterns scored visually on a lobar basis included ground‐glass opacities, reticular pattern, honeycombing, consolidation, gas trapping (which comprised separate scores of emphysema and mosaic attenuation (the decreased attenuation component)) and traction bronchiectasis …”
Section: Methodsmentioning
confidence: 99%
“…New computer algorithms utilising three-dimensional volumetric CT datasets, can quantify parenchymal pattern extents (27,28) and have been shown to better predict survival in various fibrosing lung diseases at baseline, than visual CT scores (29,30). Computer analysis also has the potential to uncover CT features hitherto under-recognised by visual CT analysis that predict mortality in IPF.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated the utility of CALIPER (Computer‐Aided Lung Informatics for Pathology Evaluation and Rating) compared with visual scoring for quantitating radiological patterns in HP against functional indices of pulmonary disease. In previous reports, the authors have shown CALIPER correlated better with physiological measures of lung disease (forced expiratory volume in 1 s, FEV 1 , and forced vital capacity, FVC) in IPF patients and for mortality prediction in connective tissue disease associated ILD (CTD‐ILD) compared with visual scores …”
mentioning
confidence: 98%